2016
DOI: 10.1097/ijg.0000000000000128
|View full text |Cite
|
Sign up to set email alerts
|

LOXL1 Gene Polymorphism With Exfoliation Syndrome/Exfoliation Glaucoma

Abstract: Our meta-analysis indicates that rs1048661 ("G" alleles) had weak association with XFG/XFS; rs3825942 ("G" alleles) had strongly association with XFG/XFS; and rs2165241("T" alleles) had significant risk with XFG/XFS in some ethnicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 45 publications
0
31
0
4
Order By: Relevance
“…Interestingly, there is evidence of nominal association for both CLU SNPs (rs3087554 in the Japanese dataset and rs2279590 in the Indian datasets) despite the differences in direction of effect, which may be caused by ‘flipping’ of the risk allele due to population specific effects (Lin et al, 2007). This is a recognized phenomenon in disease association studies including the association of LOXL1 with XFS where commonly associated SNPs are ‘flipped’ in some Asian populations and in the South Africans (Wang et al, 2014; Dubey et al, 2014; Williams et al, 2010). Alternatively, the observed associations between CLU SNPs in the Indian and Japanese populations may be spurious findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, there is evidence of nominal association for both CLU SNPs (rs3087554 in the Japanese dataset and rs2279590 in the Indian datasets) despite the differences in direction of effect, which may be caused by ‘flipping’ of the risk allele due to population specific effects (Lin et al, 2007). This is a recognized phenomenon in disease association studies including the association of LOXL1 with XFS where commonly associated SNPs are ‘flipped’ in some Asian populations and in the South Africans (Wang et al, 2014; Dubey et al, 2014; Williams et al, 2010). Alternatively, the observed associations between CLU SNPs in the Indian and Japanese populations may be spurious findings.…”
Section: Discussionmentioning
confidence: 99%
“…A genome-wide association study (GWAS) using unrelated patients and controls from Iceland and Sweden revealed significant association between common lysyl oxidase-like 1 ( LOXL1 ) variants and XFS (Thorleifsson et al, 2007). This association was subsequently replicated in populations worldwide (Wang et al, 2014), including in United States clinic-based samples (Fingert et al, 2007; Aragon-Martin et al, 2008; Challa et al, 2008; Fan et al, 2008; Yang et al, 2008). Overall, these results show that LOXL1 is a major gene associated with XFS.…”
Section: Introductionmentioning
confidence: 90%
“…31 We speculate that accumulation of XFM in the walls of digital precapillary arterioles or in nailfold capillaries produces nontubular vascular lumens that alter local hemodynamics and contribute to the tortuosity, hemorrhaging, and avascularity observed in this study. Furthermore, as elastin insulates all blood vessels in the body, insufficient elastogenesis due to altered lysyl oxidase-like 1 (LOXL1) expression 32 (strongly implicated in XFS/XFG 33,34 ) may also contribute to microvascular morphological changes. Interestingly, iris fluorescein angiography in LOXL1 knockout mice demonstrates leakage into the anterior chamber, 35 and canine carotid arteries exposed to elastase exhibit marked tortuosity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous meta-analyses on the same topic included fewer studies (Chen et al, 2010;N = 25;Tang et al, 2014;N = 12;Wang et al, 2014;N = 25;Ji et al, 2015;N = 33). More importantly, they provided results on fewer ethnic groups because of limited data at the time of the literature search (Chen et al, 2010;Wang et al, 2014) or because of different eligibility criteria and the use of broad categories to define ethnicity (Tang et al, 2014;Ji et al, 2015). With 39 independent cohorts included in the analyses we were able to synthesize data (at least two independent studies per ethnic group) for Caucasians, Japanese, Koreans, Chinese, South Asians, Middle Easterners, and Black South Africans.…”
Section: Discussionmentioning
confidence: 95%
“…The purpose of this study was to conduct a meta-analysis of published data on the association of LOXL1 polymorphisms rs3825942, rs1048661, and rs2165241 with PEX (with or without glaucoma) in different ethnic groups. Although there have been previous meta-analyses on this topic (Chen et al, 2010;Tang et al, 2014;Wang et al, 2014;Ji et al, 2015), additional data have emerged, which allow for subgroup analyses in a larger number of well-defined ethnic groups. In addition, the present work explores heterogeneity between studies and associated factors, investigates possible sources of bias, including publication bias, and assesses the quality of study methodology and the genetic quality of individual studies.…”
Section: Introductionmentioning
confidence: 93%